Long-term prognosis after acute anterior infarction with atrioventricular block. Issue 2 (February 1977) - Ginks, W R; Sutton, R; Oh, W; Leatham, A
Abstract : The purpose of this study was to evaluate the need for permanent pacing in patients who have survived the effects of anterior myocardial infarction with complete heart block and have returned to sinus rhythm but who are left with impairment of intraventricular conduction. We have reviewed 52 patients with complete heart block complicating recent anterior myocardial infarction. Temporary pacing was instituted in all patients. There were 25 hospital survivors who were followed for an average of 49 months. Long-term pacing was established in 4 patients. Of the 21 patients in sinus rhythm, 14 had partial bilateral bundle-branch block with either right bundle-branch block and left anterior hemiblock or right bundle-branch block and left posterior hemiblock; at the end of the follow-up period, 10 of these 14 were alive and well. Furthermore, permanent pacing failed to prevent sudden death in 2 patients. At the present time, therefore, we conclude that long-term pacing is not justified in patients, otherwise asymptomatic, with partial bilateral bundle-branch block persisting after transient complete heart block in anterior myocardial infarction.